Fabrication and characterization of flexible-conductive nanocomposites - Lau, Jun Jie (2016)
There is a rising enthusiasm in developing supercapacitors for the use of energy storage. The current challenge is to develop a supercapacitor that has an energy capacity comparable to traditional batteries while retaining the fast charging benefits of capacitors. The objective of this research project is to develop a novel ternary composite electrode material made up of flexible cellulose paper and metal oxide to fabricate a solid-state flexible supercapacitor. The use of lightweight and easily-fabricated MnO2/carbon nanofiber (CNF)-based flexible networks as binder-free electrodes and a PVA/H2SO4 electrolyte for the formation of stretchable solid-state supercapacitors was examined. The active electrodes were fabricated from 3D porous MnO2 assembled from cross-walled and interconnected sheet-architectural MnO2 on CNF based paper substrates. These substrates were fabricated through a simple two-step procedure involving the coating of vapor grown carbon nanofibers onto qualitative filter paper by a vacuum filtration process and subsequent electrodeposition of the interconnected MnO2 sheets onto the CNF-coated paper. The CNF/Paper serves as an active and good conductive flexible substrate for an electrode in supercapacitors. Correspondingly, the nanoporous structure by the MnO2 facilitates the effective contact range of the active material with the electrolyte, thus increasing the capacitance.